How incorporation of scents could enhance immersive virtual experiences - Ischer, Matthieu; Baron, Naëm; Mermoud, Christophe; Cayeux, Isabelle; Porcherot, Christelle; Sander, David; Delplanque, Sylvain (Frontiers in Psychology, 2014)
Under normal everyday conditions, senses all work together to create experiences that fill a typical person´s life. Unfortunately for behavioral and cognitive researchers who investigate such experiences, standard laboratory tests are usually conducted in a nondescript room in front of a computer screen. They are very far from replicating the complexity of real world experiences. Recently, immersive virtual reality (IVR) environments became promising methods to immerse people into an almost real environment that involves more senses. IVR environments provide many similarities to the complexity of the real world and at the same time allow experimenters to constrain experimental parameters to obtain empirical data. This can eventually lead to better treatment options and/or new mechanistic hypotheses. The idea that increasing sensory modalities improve the realism of immersive virtual reality environments has been empirically supported, but the senses used did not usually include olfaction. In this technology report, we will present an odor delivery system applied to a state-of-the-art IVR technology. The platform provides a three-dimensional, immersive, and fully interactive visualization environment called "Brain and Behavioral Laboratory - Immersive System" (BBL-IS). The solution we propose can reliably deliver various complex scents during different virtual scenarios, at a precise time and space and without contamination of the environment. The main features of this platform are: i) the limited cross-contamination between odorant streams with a fast odor delivery (< 500 ms), ii) the ease of use and control, and iii) the possibility to synchronize the delivery of the odorant with pictures, videos or sounds. How this unique technology could be used to investigate typical research questions in olfaction (e.g., emotional elicitation, memory encoding or attentional capture by scents) will also be addressed.